Kreatifitas Gen Z dan Reinterpretasi Bahasa Arab : Peran AI dalam Proses Pembelajaran - Aminah Aura Yunda; Shoofiyah Aliyah (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2025)
This research aims to find out how the creativity of Gen Z influences the process of reinterpreting Arabic in the context of modern learning, and to what extent the role of AI can support this process. This research uses the literature study method by analysing relevant articles to understand the concept of AI's role in gen z creativity and Arabic language reinterpretation in the learning process. Meanwhile, this research shows that the application of Artificial Intelligence (AI) in Arabic language learning is efficient and helpful in supporting the learning process. Among them can help search for materials, references, questions, journals/articles, and digital books, increase students' learning motivation because it is fun and exciting, support language practice and understanding, help practice speaking, writing, and get grammar explanations instantly, correct errors quickly, translate Arabic texts, help data analysis and understand the context of Arabic texts, support conversation exercises, provide feedback and reference sources and learning aids with features that enrich the Arabic language learning process.